2021
DOI: 10.1158/1078-0432.ccr-20-2298
|View full text |Cite
|
Sign up to set email alerts
|

Three Distinct Stroma Types in Human Pancreatic Cancer Identified by Image Analysis of Fibroblast Subpopulations and Collagen

Abstract: Purpose: Cancer-associated fibroblasts have emerged to be highly heterogenous and can play multifaceted roles in dictating pancreatic ductal adenocarcinoma (PDAC) progression, immunosuppression, and therapeutic response, highlighting the need for a deeper understanding of stromal heterogeneity between patients and even within a single tumor. We hypothesized that image analysis of fibroblast subpopulations and collagen in PDAC tissues might guide stroma-based patient stratification to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 57 publications
5
93
0
Order By: Relevance
“…Although collagen was conventionally considered as a passive barrier to resist tumor cells [33], it is now evident that collagen is also actively involved in promoting tumor progression [32]. However, according to the recent results of Ogawa et al regarding the distinct stroma types based on stromal heterogeneity, patients with collagenrich cancer stroma showed decreased MMP gene expression levels with longer survival compared with other patients with cancer stroma highly expressing CAF markers such as α-SMA or FAP [20]. We observed that the fibroblast CAF-D group appeared to act as a physical barrier that tightly surrounds the cancer cells and protects from them expanding to the surrounding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although collagen was conventionally considered as a passive barrier to resist tumor cells [33], it is now evident that collagen is also actively involved in promoting tumor progression [32]. However, according to the recent results of Ogawa et al regarding the distinct stroma types based on stromal heterogeneity, patients with collagenrich cancer stroma showed decreased MMP gene expression levels with longer survival compared with other patients with cancer stroma highly expressing CAF markers such as α-SMA or FAP [20]. We observed that the fibroblast CAF-D group appeared to act as a physical barrier that tightly surrounds the cancer cells and protects from them expanding to the surrounding.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this viewpoint, it is extremely interesting that breast cancer cell migration is dependent on collagen type I fibril alignment rather than stiffness [18] and that the collagen fibril diameter regulates cell morphology and invasiveness [19]. Interestingly, recent data have suggested that multiplex immunohistochemical (IHC) analyses of human pancreatic cancer stroma revealed a wide spectrum of phenotypical CAF variations in terms of protein expression levels of known fibroblastic markers such as α-SMA and fibroblast activation protein (FAP) [20]. In addition, they showed that welldifferentiated tumor ducts were tightly surrounded by α-SMA-dominant CAFs with thick collagen bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the whole pancreas showed diffuse signi cant uptake in some patients, which covered the tumors. As we all know, desmoplasia and in ammation are two major hallmarks of pancreatic cancer [24,25]. In this circumstance, the combination with other examinations or close follow-up is of great importance for the accurate diagnosis.…”
Section: Changes Of Clinical Decisionmentioning
confidence: 99%
“…Yet, tissue-based studies suggest that collagen- and ECM-rich stroma yields a better prognosis (Bolm et al, 2017; Erkan et al, 2008). Similarly, despite the wealth of functional studies showing that CAFs can promote PDAC progression and chemoresistance (Ligorio et al, 2019; Ogawa et al, 2021), higher stromal content can yield a better prognosis (Knudsen et al, 2017; Torphy et al, 2018) and the depletion of CAFs can result in more aggressive tumors in mice (Özdemir et al, 2015; Rhim et al, 2014). Thus, interactions between PDAC and stromal cells are likely not uniformly tumor promoting or inhibitory and the underlying intricate nuances have remained poorly understood.…”
Section: Introductionmentioning
confidence: 99%